Study on the TBR Variation Induced by Breeding Material Ratio of Water-Cooled Blanket for CFETR. (2nd January 2020) - Li, Jie; Zhang, Jie; Qiu, Yang; Zhang, Liangliang; Liu, Changle; Gao, Xiang
Abstract: The breeding material ratio (BMR) makes a significant impact on the tritium breeding ratio (TBR) to the fusion blanket due to the material fraction influence inside the blanket interior. The qualitative study on the BMR-related TBR issues are focused on the two cases of water-cooled blanket modules: the mixture blanket structure and the multilayer blanket case. The study indicates that TBR is a unique value in accordance with one BMR value in the mixture blanket. Moreover, a systematic scheme on TBR estimation based on multiple variable combinations is carried out for the multilayer model. It is found that the blanket local TBR would vary along with BMR increasing, and that high TBRs are obtained at BMR in the range of 0.08 to 0.12 for the two cases. In particular, the maximum TBR occurs when the BMR is in the range of 0.09 to 0.1. Furthermore, TBR variation due to BMR change induced by blanket macrofactors, like material type, material ratio, material structure, etc., is defined using the universal function solution. These results would be more important to the breeding blanket design and optimization since they would affect the blanket structure concepts and their TBR estimations. Hence, the blanket BMR issues are important concerns on the road toward an advanced blanket system for the Chinese Fusion Engineering Test Reactor (CFETR) at the present pre-engineering stages.